CORDULA: Software Requirements Extraction Utilizing Chatbot as Communication Interface - Friesen, Edwin; Bäumer, Frederik Simon; Geierhos, Michaela (Joint Proceedings of REFSQ-2018 Workshops, Doctoral Symposium, Live Studies Track, and Poster Track co-located with the 23rd International Conference on Requirements Engineering: Foundation for Software Quality (REFSQ 2018))
Natural language requirement descriptions are often unstructured, contradictory and incomplete and are therefore challenging for automatic processing. Although many of these deficits can be compensated by means of Natural Language Processing, there still remain cases where interaction with end-users is necessary for clarification. In this paper, we present our idea of using chatbot technology to establish end-user communication in order to support the automatic compensation of some deficits in natural language requirement descriptions.

Back to Basics: Extracting Software Requirements with a Syntactic Approach - Caron, Matthew; Bäumer, Frederik Simon; Geierhos, Michaela (Joint Proceedings of REFSQ-2018 Workshops, Doctoral Symposium, Live Studies Track, and Poster Track co-located with the 23rd International Conference on Requirements Engineering: Foundation for Software Quality (REFSQ 2018))
As our world grows in complexity, companies and employees alike need, more than ever before, solutions tailored to their exact needs. Since such tools cannot always be purchased off-the-shelf and need to be designed from the ground up, developers rely on software requirements. In this paper, we present our vision of a syntactic rule-based extraction tool for software requirements specification documents. In contrast to other methods, our tool will allow stakeholders to express their needs and wishes in unfiltered natural language, which we believe is essential for non-expert users.

Vorwort des Dekans. Für Jutta Ströter-Bender - Peckhaus, Volker (Kulturelles Erbe. Erinnern, Erzählen, Erfinden. Festschrift für Prof. Dr. Jutta Ströter-Bender)

David Hilberts axiomatisches Programm und die kritische Philosophie - Peckhaus, Volker (Mitteilungen der Mathematischen Gesellschaft in Hamburg)
Rezension: Math. Rev. MR3888577 (Martin David Davis); Zbl. Math. 1310.01017 (Reinhard Siegmund-Schultze)

Reinhold, Christian Gottlieb Ernst Jens - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 7: Re–Te)

Weierstraß, Karl Theodor Wilhelm - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 8: Th–Z)

Wiener, Ludwig Christian - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 8: Th–Z)

Zermelosches Axiom - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 8: Th–Z)

Verknüpfung - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 8: Th–Z)

Scholz, Heinrich - Peckhaus, Volker (Stanford Encyclopedia of Philosophy (Fall 2018 Edition))

Georg Cantor und die Anfänge der Grundlagenforschung [Abstract] - Peckhaus, Volker (Gemeinsame Jahrestagung GDM und DMV 2018. Paderborn, 5.-9. März 2018. Book of Abstracts)

Terrorismus und Folter – Reflexionen der Gegenwartsliteratur am Beispiel von Christoph Peters’ Ein Zimmer im Haus des Krieges und Dorothea Dieckmanns Guantánamo - Willeke, Stephanie (Menschenrechte im Konflikt. Kulturkampf, Meinungsfreiheit, Terrorismus (Schriften der Arbeitsstelle Menschenrechte der Otto-zu-Guericke-Universität Magdeburg))

„Ein obskures Vexierbild der Antigone. Versuch über ein widerständiges Nachleben der Antigone des Sophokles im Kontext von Georges Didi-Hubermans Das Nachleben der Bilder“ - Böker, Ines (Sulle tracce di Antigone. Diritto, letteratura e studi di genere)

Alltagsstrategien zur Rezeption einer Linguistic Landscape und erste Überlegungen zur Förderung im Unterricht - Ballweg, Sandra (Linguistic Landscape und Fremdsprachendidaktik. Perspektiven für die Sprach-, Kultur- und Literaturdidaktik)

Forschungsmethodische Überlegungen zur Nexusanalyse in einem Projekt zu family language policies in mehrsprachigen Familien - Ballweg, Sandra (Darmstädter Vielfalt. 10 Jahre Fachgebiet Sprachwissenschaft - Mehrsprachigkeit)

Planung einer Unterrichtseinheit - Ballweg, Sandra (Unterrichtsmanagement (= Kompendium DaF/DaZ 6))

Fachunterricht in der sogenannten Regelklasse berufsbildender Schulen aus der Perspektive neu zugewanderter Schülerinnen und Schüler: Anforderungen und Ressourcen - Havkic, Amra; Dohmann, Olga; Domenech, Madeleine; Niederhaus, Constanze (Neuzuwanderung und Bildung. Eine interdisziplinäre Perspektive auf Übergänge in das deutsche Bildungssystem)

Sprache(n) gemeinsam bewusstmachen. Language Awareness und Peer Learning - Freitag, Dagmar; Havkic, Amra; Niederhaus, Constanze; Westphal, Petra (Peer Learning als Element einer diversitysensiblen, inklusiven Bildung an Hochschulen)

Ansätze des Integrierten Fach- und Sprachlernens in der beruflichen Bildung - Niederhaus, Constanze (Sprache und Kommunikation in der beruflichen Aus- und Weiterbildung. Ein interdisziplinäres Handbuch)

Die Sprachen der Schülerinnen und Schüler wertschätzen und einbeziehen - Niederhaus, Constanze; Havkic, Amra (DaZ/DaF-Didaktik. Praxishandbuch Sekundarstufe I und II)